(untitled) (Progressive Agriculture, 2021)
Vermicompost has various positive effects on soil, particularly soil fertility and productivity. Two experiments were conducted at farmer’s field of Mymensingh and Jamalpur to observe the effect of vermicompost on cabbage production during rabi season 2019. There were seven compost treatments viz: T1: RCF (N150 P40 K100 S16 Kg ha-1), T2: 85% RCF, T3: 70% RCF, T4: 85% RCF + 3 t ha-1 vermicompost (VC), T5: 85% RCF + 1 t ha-1 VC, T6: 70% RCF + 3 t ha-1 VC and T7: 70% RCF + 1 t ha-1 VC. The experiments were laid out in a RCBD (Randomized Complete Block Design) with three replications. The average fresh yield at Mymensingh ranged from 36.5 to 61.6 t ha-1 with the highest yield of 61.6 t ha-1 from treatment T4 (85% RCF + 3 t ha-1 VC). At Jamalpur, the average yield ranged from 33.5 to 55.2 t ha-1 and the highest yield of 55.2 t ha-1 was recorded from treatment T4 (85% RCF + 3 t ha-1 VC). The lowest yield was obtained from treatment T3 in both the location. The percent fresh yield increased over control (T1), was 22.70 and 20.78 in Mymensingh and Jamalpur, respectively. The highest gross margin is Tk. 829007/-, which is obtained from treatment T4 (85% RCF + 3 t ha-1 VC). The highest MBCR 2.76 (average of two locations) was obtained from the same treatment T4 (85% RCF + 3 t ha-1 VC). Result indicated that application of vermicompost along with 85% recommended dose of chemical fertilizer is more profitable than application of chemical composts only. Progressive Agriculture 31 (3): 190-194, 2020